Pengaruh Bahasa Asing terhadap Bahasa Indonesia dalam Komunikasi Digital: Kajian Integrasi dan Interferensi - Poppy Adelia Adisty; Ines Amelia; Andini Aulia Distira; Aulia Uswatun; Ayu Nadira Wulandari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The development of technology and digital media has influenced the way people communicate, particularly through chat applications such as WhatsApp. In digital communication, the use of Indonesian is often mixed with foreign languages, especially English. This phenomenon leads to the processes of language integration and interference. Integration occurs when elements of a foreign language are absorbed and used naturally in Indonesian, whereas interference occurs when elements of a foreign language influence the structure or usage of Indonesian so that it deviates from established linguistic norms. This study aims to analyze the forms of language integration and interference that appear in digital communication. The research employs a descriptive qualitative method, with data collected through observation of chat conversations on digital media. The results show that the use of foreign vocabulary in digital communication occurs due to factors such as practicality, user habits, and the influence of globalization. This phenomenon indicates that digital communication has become a space that accelerates language mixing, both in the form of integration and interference. Therefore, understanding these two phenomena is important for examining the dynamics of the development of the Indonesian language in the digital era.